2005
DOI: 10.1021/jf0507700
|View full text |Cite
|
Sign up to set email alerts
|

Wet Deposition of Current Use Pesticides at a Rural Location on the Delmarva Peninsula:  Impact of Rainfall Patterns and Agricultural Activity

Abstract: Event-based precipitation samples were collected during the main agricultural season (April-September) over 4 years (2000-2003) at one site in the Choptank River Watershed on the Delmarva Peninsula. The samples were analyzed for 19 agricultural pesticides to determine the contribution of wet deposition as a source of these compounds to the Chesapeake Bay and the factors affecting the temporal trends in deposition. Chlorothalonil was detected most frequently (92% samples) followed by metolachlor (66%) and endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Pesticides have also been reported in rain water samples in other countries. 27,[46][47][48][49][50] These results highlight the possible impacts of pesticide deposition on aquatic and terrestrial ecosystems. Considering that pesticides can be dispersed in the atmosphere, the intensive use of pesticides in the study area could affect other remote and important natural ecosystems, such as the Pantanal.…”
Section: Occurrence Of Pesticides In Rain Watermentioning
confidence: 86%
“…Pesticides have also been reported in rain water samples in other countries. 27,[46][47][48][49][50] These results highlight the possible impacts of pesticide deposition on aquatic and terrestrial ecosystems. Considering that pesticides can be dispersed in the atmosphere, the intensive use of pesticides in the study area could affect other remote and important natural ecosystems, such as the Pantanal.…”
Section: Occurrence Of Pesticides In Rain Watermentioning
confidence: 86%
“…Pesticides are biologically active compounds designed to interfere with metabolic processes (Matsumura, 1985;Manahan, 1994). The detection of pesticide in soil, water and air (Hoffman et al, 2000;Goel et al, 2005;Harman-Fetcho et al, 2005;Loague et al, 2006;Lv et al, 2010;Riederer et al, 2010;Weber et al, 2010;Hayward et al, 2010), and reported adverse effects of pesticides to non-target organisms at environmentally relevant levels (Chandler et al, 1991;Clark et al, 1993;Margni et al, 2002;Schulz, 2004) has invoked public concern. The off-site transport of pesticides and soil with runoff from agriculture is believed to be a large contributor to water quality degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing population in the Baltimore-Washington corridor exerts significant pressure on the health of this complex ecosystem. Sediments, nutrients, and other toxic chemicals enter the Chesapeake Bay via the atmosphere and the 150 major rivers and streams that feed the estuary, and studies have demonstrated that industrial and agricultural pollutants are entering the Chesapeake Bay through both riverine [1][2][3], and atmospheric sources [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These data were examined along with measured toxicity, sediment characterization, benthic community analysis, and other key parameters such as dissolved oxygen. Their report indicates that concentrations of metals and organic pollutants such as polychlorinated biphenyls (PCBs), polyaromatic hydrocarbons (PAHs), and the pesticides, 1-chloro-4-[2,2,2-trichloro-1-(4-chlorophenyl) ethyl]benzene (4,4 0 -DDT) and chlordane, were positively correlated with toxicity response. Researchers working in the nearby Delaware River and Delaware Bay found that concentrations of the organic contaminants 4,4 0 -DDE, heptachlor epoxide, chlordanes, and total PCBs) were predictive of hatching success for osprey (Pandion halieatus) [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation